Polyploidy, genome size variation and diversification in an autopolyploid complex: the case of Turnera sidoides (Passifloraceae, Turneroideae). Issue 1 (31st December 2022) - Luque, Juan M. Roggero; Moreno, E. M. Sara; Kovalsky, Ivana E.; Seijo, J. Guillermo; SolÍs Neffa, Viviana G.
Abstract : Polyploidy is a major force in plant evolution. The possession of more than two chromosome complements may affect the genetic and genomic constitution and the phenotypes of polyploids, having consequences for their ecology, geography and diversification. Here, we used Turnera sidoides autopolyploid complex to assess the effect of polyploidy on genome size and on the diversification of this species. The remarkable diversity in habitat preferences, ploidy levels and multiple independent origins of polyploids, make this complex a suitable model for disentangling the effects of phylogenetic relationships and environmental conditions on the variation in genome size. We used an integrative approach comprising genome size estimations in 53 (diploid to hexaploid) populations of the different subspecies and morphotypes of T. sidoides, a molecular phylogenetic reconstruction and a biogeographical analysis to identified closely related diploids and polyploids that remained in the same habitat aiming to answer the following questions: 1) does polyploidy per se induce a significant change of the Cx-value?; 2) is the Cx-value variation an adaptive response/consequence to different environmental gradients?; and 3) does polyploidy enable the range expansion of diversified diploid lineages within the same ecoregion?. Comparisons of Cx-values among phylogenetically related diploids–polyploids provided evidence that polyploidy is not the main factor determining the Cx variation. Instead, the Cx-values varied associated with few climatic variables along latitudinal and climatic gradients, suggesting that variation in genome size would have been an adaptive response to different habitats. The analysis of the environmental preferences of diploid and polyploids within each lineage provides evidence that autopolyploidy further promoted the range expansion of the already diversified diploids. These results together with the morphological constancy among different cytotypes within lineages suggest that autopolyploidy per se did not contribute significantly to the morphological and taxonomic diversification, but enabled further range expansion of lineages within the complex.